2017
DOI: 10.1007/s11010-017-3061-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced abnormalities of mitochondrial function in rat brain cortex: the effect of n-3 fatty acid diet

Abstract: Diabetic encephalopathy, a proven complication of diabetes is associated with gradually developing end-organ damage in the CNS increasing the risk of stroke, cognitive dysfunction or Alzheimer's disease. This study investigated the response of rat cortical mitochondria to streptozotocin-induced diabetes and the potential for fish oil emulsion (FOE) to modulate mitochondrial function. Diabetes-induced deregulation of the respiratory chain function as a result of diminished complex I activity (CI) and cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…In a previous report, a reduction in the phosphorylation of AMPK was found in diabetic encephalopathy. Dietary fish oil emulsion administration was shown to restore p-AMPK levels to preserve mitochondrial complex activity but was unable to prevent the shift toward saturated fatty acids in the cardiolipin composition [ 31 ]. This evidence suggests that AMPK regulates mitochondrial respiratory complexes in some diseases, but does not influence the cardiolipin pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous report, a reduction in the phosphorylation of AMPK was found in diabetic encephalopathy. Dietary fish oil emulsion administration was shown to restore p-AMPK levels to preserve mitochondrial complex activity but was unable to prevent the shift toward saturated fatty acids in the cardiolipin composition [ 31 ]. This evidence suggests that AMPK regulates mitochondrial respiratory complexes in some diseases, but does not influence the cardiolipin pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Neurons are especially vulnerable to mitochondrial stress since the energy stress-induced diversion of the physiological metabolic program of preferential utilization of glucose for regeneration of glutathione in the pentose phosphate cycle to the glycolytic pathway can weaken the antioxidant defense of neurons [ 90 , 91 ]. The hypothesis of excessive ROS production in DM is widely supported by evidence of damage to proteins, lipids, and DNA [ 92 , 93 , 94 ]. However, a significant decrease in mitochondrial membrane potential (Δψ m ), mitochondrial respiration, the enzymatic activities of the respiratory chain, and energy levels were reported in the cortex and hippocampus of diabetic rodent models [ 86 , 93 , 95 ], diabetic sensory neurons [ 96 ], or diabetic islets from humans and rodent models [ 97 , 98 ].…”
Section: Insulin–mitochondria–ros Interplaymentioning
confidence: 99%
“…The hypothesis of excessive ROS production in DM is widely supported by evidence of damage to proteins, lipids, and DNA [ 92 , 93 , 94 ]. However, a significant decrease in mitochondrial membrane potential (Δψ m ), mitochondrial respiration, the enzymatic activities of the respiratory chain, and energy levels were reported in the cortex and hippocampus of diabetic rodent models [ 86 , 93 , 95 ], diabetic sensory neurons [ 96 ], or diabetic islets from humans and rodent models [ 97 , 98 ]. On the contrary, increased ROS signaling and membrane hyperpolarization have been found in peripheral diabetic cell cultures [ 99 ].…”
Section: Insulin–mitochondria–ros Interplaymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the study indicated a mild association of diabetes and alzhiemer's type of dementia in males (Kadohara et al, 2017). Some of the animal studies have an indiacted association between diabetes and dementia ar molecular levels (Chomova et al, 2017). Eberhardt and Topka (2017) proposed that if prediabetes is managed well, that can lead to the prevention of the cognitive decline in these patients along with other neuropathological derangements.…”
Section: Introductionmentioning
confidence: 99%